Pengaruh Promosi Dan Harga Di Media Sosial Terhadap Keputusan Pembelian Rumah Subsidi Di Tikung Planet Green Tiara (Tikung Alam Raya) - Riswanda Imawan, Vikhi; Shofia Maulida, Indira; Susanti, Ike; Ruswaji (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
Population growth, especially in Indonesia, is increasingly rapid every year. With the increase in population, the need for land for residence also increases, resulting in intense competition in the subsidized housing industry in Indonesia. In this case, promotions and prices play an important role in shaping purchasing decisions, especially on social media. This research aims to determine the influence of promotions and prices on social media on purchasing decisions for subsidized housing in Tikung Planet Green Tiara, Lamongan. This type of research uses a quantitative approach, with promotion and price as independent variables, while purchasing decisions as the dependent variable. The population in this research is all consumers who live in subsidized houses on Planet Green Tiara, totaling 505 consumers, with the number of samples taken being 100 respondents. Data collection methods use survey methods, observation and distribution of questionnaires. Then the data analysis technique uses a multiple correlation test, namely the T test and F test with the help of SPSS version 26. The test results show that the T test for the Promotion variable on purchasing decisions obtained Tcount (4.992) > Ttable (1.984), which means there is an influence of promotion on partial and significant purchasing decisions. The price variable on purchasing decisions is obtained by Tcount (7.777) > Ttable (1.984), meaning that there is a partial and significant influence of price on purchasing decisions. Then from the multiple linear regression testY= 1.534+0.378X1+0.717X2, it can be concluded that the price variable has the most dominant influence on purchasing decisions.